2017
DOI: 10.1089/acu.2017.1236
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent 96-Hour Auricular Electroacupuncture for Hot Flashes in Patients with Prostate Cancer: A Pilot Study

Abstract: The hot flash is a common vasomotor disorder that causes distress in menopausal women and that can be debilitating in men with prostate cancer who are treated with androgen deprivation therapy (ADT). The utility of auricular electroacupuncture (AEA) was tested exclusively for a small cohort of men with ADT-induced vasomotor symptoms while the men underwent a course of curative radiotherapy. Prior to and during radiotherapy treatment, men with vasomotor symptoms were given repeated questionnaires regarding seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We have shown that the use of an intermittent 96 hour treatment with AEA appears to be very effective for a small cohort of men with hot flashes [1]. In 10 subjects there were highly significant improvements of the quality of life, sleep, and hot flash frequency and duration over the six weeks of the protocol study.…”
Section: Intermittent 96 Hour Auricular Electroacupuncture: a New Trementioning
confidence: 89%
See 1 more Smart Citation
“…We have shown that the use of an intermittent 96 hour treatment with AEA appears to be very effective for a small cohort of men with hot flashes [1]. In 10 subjects there were highly significant improvements of the quality of life, sleep, and hot flash frequency and duration over the six weeks of the protocol study.…”
Section: Intermittent 96 Hour Auricular Electroacupuncture: a New Trementioning
confidence: 89%
“…In a recent publication we describe the major subjective improvement of hot flashes and sleep disruption caused by hormone blockade in prostate cancer patients treated with Auricular Electro Acupuncture (AEA) [1]. Hot flashes are troublesome vasomotor symptoms caused by gender hormone withdrawal that can be caused by androgen depravation therapy (ADT) [2], in breast cancer survivors after chemo/hormonal therapy [3], or naturally in menopausal women [4].…”
Section: Where Do Hot Flashes (An Autonomic Disorder) Come From?mentioning
confidence: 99%
“…Several sham-controlled RCTs on acupuncture for a variety of clinical conditions suggest that it is more efficacious than sham in reducing sympathetic tone as measured by HRV [57,71,72]. Previous clinical research showed that AEA resulted in improvement in HRV LF/HF ratios over the course of the protocol intervention, implying improved sympathovagal balance [44]; however, this was measured using ambulatory HRV monitoring, which has not been validated against the gold standard of electrocardiogram (ECG) recordings. To date, the effect of acupuncture on HRV in women with PCOS has not been evaluated, although electro-acupuncture improved HRV and restored oestrous cycling compared to sham handling in a recent rat study [73].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention in this arm is AEA using a fixed protocol that is informed by both Chinese medical and medical acupuncture principles based on a literature review and expert consensus on the traditional and physiological indications of the points. A pilot study suggests that a novel device, the "Neurova TM " (NESI Corp), may be effective for hot flushes from androgen-deprivation therapy, a condition underpinned by sympathetic hyperactivity [44]. This method involves insertion of indwelling needles into the concha of the ear and delivery of intermittent electrical impulses over 96 h by a small battery-powered device that is worn just below the ear.…”
Section: Auricular Electro-acupuncture Stimulationmentioning
confidence: 99%
“…The articles by Harding et al [21], Valois et al [22] and Rich et al [23] also brought sleep disorder symptom. Patients with cancer often have this disorder, with an incidence of around 30-50%, compared to 15% of the general population [24], negatively impacting QoL because it affects well-being [3].…”
Section: Acupuncture As An Intervention For the Side Effects Of Cancer And Treatmentmentioning
confidence: 99%